Sciducio: a practical framework for guiding the development and leadership of the academic research environment - Stoner, Lee; Paterson, Craig; Perry, Lane; Higgins, Simon; Woolard, Nathan; Pagan Lassalle, Patricia; Cowley, Emma; Lassalle, Yolanda (Frontiers in Research Metrics and Analytics, 2023)
The goal of this paper is to introduce Sciducio, a practical framework for guiding the development and leadership of an academic research environment. The principal audience for this framework is new academics, that is individuals beginning a tenure-track position in the U.S or a lecturing position elsewhere in the world. However, we also believe this framework will be of use to established academics searching for structure, academics moving to a new institution, and can serve as a training tool for doctoral and postdoctoral trainees. We briefly describe the theory supporting Sciducio, outline the framework and its individual components (blocks), then provide suggested instructions for use. We provide suggested instructions (i.e., descriptive rather than prescriptive), because there is no one-sizefits-all approach for ensuring success. Sciducio incorporates three domains (Plan, Manage, and Deliver), encompasses eight blocks, and is intended to fit on one-sheet of paper or one screen. The Plan domain includes the blocks: value, strategy, and leadership. The Manage domain includes the blocks: activities, key resources, and finances. The Deliver domain includes the blocks: solution and channels. Considering each of the framework blocks is complex, we cannot provide full justice to each component. This paper serves as a general overview and subsequent papers will be more topic specific. Additionally, we encourage others to contribute to and advance this framework.